50 Years of Modelling Second Temple Judaism: Whence and Wither? - Klostergaard Petersen, Anders (Journal for the study of Judaism in the Persian, Hellenistic, and Roman period, 2019)
The first section describes the major progress in the study of Second Temple Judaism during the past fifty years, since A.S. van der Woude founded the Journal for the Study of Judaism. This part—the whence—comprises the main bulk of the argument. It also paves the way for the conclusion—the wither. There, I present some ideas potentially leading to new advances in the field. I call for an engagement with the social and natural sciences based on a gene-culture coevolutionary paradigm. In particular, adopting a biocultural evolutionary perspective makes it possible to situate the field and its empirical focus in a much larger context. Thereby, we shall be able to tackle some of the pivotal questions with which our scholarly predecessors wrestled. Finally, I discuss emotional studies that may help us to get a better grasp on a traditionally moot question in the texts we study.